Effects of rot-promoting bacteria on decomposition characteristics of corn straw and spring soybean yield in Saline-alkali Land - Wang, Yuqing; Zhang, Mingcong; Lu, Lei; Wang, Chen; Wang, Jianing; Hu, Yang; Li, Siyan; Xie, Wei; Hu, Xiwen; Guo, Haiqing (Frontiers in Plant Science, 2025)
Understanding the relationship between microbial inoculants and straw decomposition is crucial for achieving a high soybean yield in northern China’s cold region. This study investigated the effects of different microbial inoculants on nutrient release characteristics and extracellular enzyme activities. A pot experiment was conducted over two growing seasons (2023 and 2024) using the soybean (Glycine max L. Merrill) cultivar Nongqing 28, the saline-alkali soil as the test soil, and corn straw as the test straw. The microbial inoculants tested were Bacillus sp. ND1 and Bacillus sp. ND2. The following treatments were employed: straw with no microbial agent application (CK), straw with Bacillus sp. ND1 application (T1), straw with Bacillus sp. ND2 application (T2), and straw with a 1:1 application of Bacillus sp. ND1 and Bacillus sp. ND2 compound bacteria (T3).The two-year results showed that the T1, T2, and T3 treatments significantly increased the rate of straw decomposition, reduced the lignocellulose content, and progressively released nitrogen, phosphorus, and potassium from the straw compared to the CK. During both years, the T3 treatment exhibited the highest straw decomposition rate and enzyme activity at R2(Full Bloom period), R4(Full Pod period), R6(Full Seed period) and R8(Full Maturity period) periods, which ultimately increased soybean yield by 24.00%-28.00% (P<0.05). These findings indicate that microbial inoculants have significant potential for application in straw management and provide an important basis for optimizing straw return and crop yield. In summary, T3 treatment can accelerate straw decomposition and nutrient release rates, increase soybean yield, and provide a theoretical basis for optimizing the straw decomposition effect and rational utilization of organic resources by promoting the activity of extracellular enzymes and the degradation of straw cellulose, hemicellulose, and lignin.